Fish biodiversity and assemblages along the altitudinal gradients of tropical mountainous forest streams - Soo, Chen Lin; Lee Nyanti; Nur Ezaimah Idris; Ling, Teck Yee; Sim, Siong Fong; Jongkar Grinang; Tonny Ganyai; Lee, Karen Suan Ping (Springer Nature, 2021)
Knowledge of the fundamental aspects of ecology such as the patterns of fsh species distribution and biodiversity in the forest streams is the frst and basic step to develop efective conservation strategies. Yet, studies on altitudinal changes of fsh composition and assemblages in Bornean forest streams are scarce despite being one of the hotspots of biodiversity conservation. Hence, surveys on freshwater fsh composition along the altitudinal gradients of the Baleh River Basin in Sarawak, Borneo were conducted from April 2014 to August 2015. The Baleh River Basin was divided into seven altitudinal groups with a total of 72 stations. Group elevation ranged from 53 to 269 m above sea level. The fsh samples and environmental parameters were taken concurrently during samplings. A total of 3565 specimens belonging to six orders, 14 families, and 76 species were found in the present study. The most dominant family in the Baleh River Basin was Cyprinidae (74.4%), followed by Gastromyzontidae (16.2%) while the most dominant species was Tor tambra (12.9%), followed by Lobocheilos ovalis (12.3%). Fish abundance signifcantly higher at high altitude sites than those at low altitude sites except for Mengiong River which has the lowest fsh abundance despite with high elevation. Species richness was found signifcantly lower in midstream segment. Noticeable altitudinal gradient of fsh assemblages was observed along the Baleh River except a discontinuity at the midstream segment which is attributable to the poorer quality infow from the Mengiong River coupled with the meandering feature of the segment. Fish abundance was signifcantly and positively correlated with elevation, water pH and conductivity while negatively correlated with turbidity. Anthropogenic activities in the Baleh River Basin had altered the environmental variables thus disrupted the altitudinal gradient of fsh assemblages. This phenomenon is apparent when the Canonical Correspondence Analysis (CCA) revealed that the frst axis (CCA1) explained 42.5% of the variation and has positive loading on dissolved oxygen (DO) and negative loading on water conductivity; whereas CCA2 explained 37.5% of the variation and positively loaded on elevation, water pH, and DO. The results demonstrated that Gastromyzon fasciatus preferred more oxygenated water than Protomyzon sp., G. sp 1, and G. punctulatus although they are all from Gastromyzontidae family that inhabiting high altitude sites. Barbonymus schwanenfeldii was also found most abundant with elevated dissolved oxygen value. On the other hand, Rasbora volzii and R. hosii inhabiting lower altitude sites with less oxygenated and more acidic water.